«Ничто-ничто не пропадает»: Михаил Владимирович Безродный (16 февраля 1957 — 18 ноября 2023) [“Nothing is Lost, Nothing Whatever”: In Memoriam Michail Bezrodnyj (February 16, 1957 — November 18, 2023)] - Leving, Yuri (Slavica Revalensia, 2023)
This is an obituary for Dr. Michail Bezrodnyj of Heidelberg University, a scholar and a man of letters, whose debut book End of the Quote (1996) is regarded as one of the major achievements of contemporary Russian literature.